Edmund Husserl's Phenomenology: An Approach Offer in Islamic Studies - Wardah Nailul Qudsiyah; Achmad Khudori Soleh (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
Analyzing the nature of meaning always becomes a crucial issue in a religious phenomenon. The need for a compatible approach to the problem of diverse social phenomena is important to discuss. This study aims to analyze a methodological offer adapted from a phenomenologist, Edmund Husserl. This library research traced and analyzed data from various written sources such as books, journal articles, etc. The results of this study indicate that: (1) as a research method, phenomenology describes the meaning of life experiences for some individuals about a concept or phenomenon, and explores the structure of consciousness in human experience; (2) Husserl's phenomenology mainly focuses on the concept of reduction, namely a process of setting aside all assumptions and prejudices about phenomena; and (3) phenomenological researchers have to be able to go deep into the religious experience of each individual to the final stage of the transcendental consciousness appears in researchers. Thus, researchers have to build closeness with informants.